(untitled) (Journal of the College of Basic Education, 2023)
This research comes within the context of the survey descriptive approach, which aimed at a survey descriptive study of the levels of cognitive depth among students of the Department of Mathematics in the Colleges of Basic Education by answering the following questions: What are the levels of cognitive depth among students of the mathematics department in the faculties of basic education? In order to achieve the objectives of the research and answer its questions, a number of null hypotheses were developed. The basic sample was chosen by the stratified random method, where the basic sample amounted to (330) male and female students of the fourth stage in the Department of Mathematics in the faculties of Basic Education, with a percentage (30%) of the total community of (1108) distributed over seven universities (Al-Mustansiriya, Mosul, Kufa). Tikrit, Diyala, Maysan, Tal Afar). One division was selected from each of the mathematics departments in the faculties of basic education In order to achieve the objectives of the research, the researcher took the following actions: Preparing a test for cognitive depth at its four levels (remembering and reproduction, application of concepts and skills, strategic thinking, extended thinking), which consists of (40) objective paragraphs of the type of multiple choice distributed on the four levels, and by (10) paragraphs for each level, and it was verified From its sincerity and stability, where the stability of the test reached (0.83). The research tool (the cognitive depth test) was applied to the main research sample, and using the appropriate statistical means, the results showed the following: There is a weakness in the possession of the students of the Department of Mathematics in the Colleges of Basic Education in the levels of cognitive depth. In light of the results of the research, the researcher recommended several recommendations, including: holding seminars and training courses for students to demonstrate the importance of levels of knowledge depth, encourage them to use them, and train mathematics teachers to formulate questions in the four levels of depth of knowledge. levels of cognitive depth.